GUIDELINES FOR RATIONALIZATION OF MANAGEMENT OF PERFORMANCE OF LOGISTICS SYSTEM OF TRANSPORT MACHINE MANUFACTURING ENTERPRISES - Yulia A. Anankina (Статистика и экономика)
The main problems that occurs in a process of movement of material flows in the enterprises of transport machine manufacturing enterprises are stated in the article. Particular attention is paid to the rational use of vehicles on the existing capacity of the material flow of the enterprise. Process of transport service of material flow is concerned step by step. The place of transport in the logistics enterprise system is determined by authors. We give guidelines for rationalization of management of performance of logistics system of transport machine manufacturing enterprises in the context of compliance capacity utilization with the current provision of transport.